2005
DOI: 10.1007/s00414-005-0030-5
|View full text |Cite
|
Sign up to set email alerts
|

Early increase in TNF-alpha-containing mast cells in skin lesions

Abstract: We have evaluated the numbers and immunohistochemical positivity for tumor necrosis factor (TNF) alpha of the mast cells in (a) 40 skin samples collected at autopsy from subjects who had survived for a few seconds to 1 h, (b) 10 samples of post-mortem skin lesions and (c) 10 surgical biopsies of healthy skin. Sections were treated with fluoresceinated avidin, to tag mast cell granules, followed by indirect immunohistochemistry for TNF-alpha with polyclonal primary and rhodaminated secondary antibodies. We coul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 29 publications
1
17
0
Order By: Relevance
“…The knowledge of macroscopic and histological findings should be of special interest for all those who perform autopsies in these victims [22]. The exact pathogenesis of OHSS remains a mystery, so in the diagnostic suspicion of OHSS, the forensic pathologist must use all the modern laboratory armament to validate the diagnosis in the extremely rare fatal cases due to this syndrome [23][24][25][26].…”
Section: Discussionmentioning
confidence: 98%
“…The knowledge of macroscopic and histological findings should be of special interest for all those who perform autopsies in these victims [22]. The exact pathogenesis of OHSS remains a mystery, so in the diagnostic suspicion of OHSS, the forensic pathologist must use all the modern laboratory armament to validate the diagnosis in the extremely rare fatal cases due to this syndrome [23][24][25][26].…”
Section: Discussionmentioning
confidence: 98%
“…The molecular and cellular pathophysiology of the wound healing process is applied for wound age determination. Recently, the immunohistochemical detection and RNA analyses of several molecules (e.g., extracellular matrix components, growth factors, cytokines, and adhesion molecules) has become a powerful method for forensic practices such as wound age determination or postmortem diagnosis [3][4][5][6][7][8][9][10][11][12][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45]. To the best of our knowledge, there have been only two forensic studies on thrombus age estimation Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we have observed down-regulated TNF expression among individuals with arsenical skin lesions and down-regulated expression of CCL20, providing credence to the suppression of a chemokine response pathway in arsenic toxicity. There is evidence to indicate that TNF is released early in response to skin wounds or inflammation (69), which may suggest that the downregulated expression of TNF observed in arsenical skin lesion cases is also indicative of deficient wound healing.…”
Section: Discussionmentioning
confidence: 99%